Cytotoxic Guanidine Alkaloids from Pterogyne nitens - Regasini, Luis Octavio [UNESP]; Castro-Gamboa, Ian [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Furlan, Maysa [UNESP]; Barreiro, Eliezer Jesus; Pinheiro Ferreira, Paulo Michel; Pessoa, Claudia; Costa Lotufo, Leticia Veras; Moraes, Manoel Odorico de; Marx Young, Maria Claudia; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2009)
As part of a bioprospecting program aimed at the discovery of potential anticancer drugs, two new guanidine-type alkaloids, nitensidines D and E (1, 2), and the known pterogynine (3), pterogynidine (4), and galegine (5), were isolated from the leaves of Pterogyne nitens. The structures of I and 2 were established on the basis of spectroscopic data interpretation. These compounds were tested against a small panel of human cancer cell lines. Compound 2 exhibited cytotoxicity for HL-60 (human myeloblastic leukemia) and SF-245 (human glioblastoma) cells.